Legal Framework and Ethical Considerations in International Sports Aviation: A Comparative Study of Regulatory Compliance - Gevan Naufal Wala; Lazarev Viktor Antonovich (Siber Nusantara Review, 2025)
Sports aviation has emerged as a rapidly growing sector requiring comprehensive legal frameworks to ensure safety, ethical compliance, and regulatory harmonization across jurisdictions. This study examines the comparative legal frameworks governing international sports aviation in the United States, European Union, Australia, and Indonesia, analyzing their regulatory compliance mechanisms and ethical considerations. Employing a qualitative comparative legal research methodology, the study analyzes primary legal documents, international conventions, and secondary sources from academic literature. Results indicate significant inconsistencies in regulatory frameworks across jurisdictions, with variations in safety standards, certification requirements, and enforcement mechanisms. Ethical considerations including safety ethics, environmental protection, fair competition, and data privacy emerge as critical components requiring greater attention in regulatory design. The study identifies best practices from jurisdictions with effective compliance mechanisms and proposes recommendations for harmonizing international sports aviation regulations. Findings contribute to international sports law literature and provide practical guidance for policymakers seeking to enhance regulatory effectiveness while balancing innovation and safety in sports aviation.